Master Teachers’ Experiences and Perceptions of Educational Reforms: Case Studies of Three Rural Science Teachers - Bryan, Joshua Thomas (My University, 2013)
In the current era of school reforms, teachers are being asked to make decisions regarding instruction and school improvement that they were not hired to perform, nor prepared to perform (Elmore, 2002). The discrepancies between teacher motivation to become teachers and the requirements for success are causing many teachers to leave the profession. Qualitative case study research was conducted to discover the experiences and perceptions of three master science teachers with regard to the changes that have occurred over the course of their careers and the adoption of the Common Core State Standards and the Next Generation Science Standards. Through the case study analysis and the resulting cross-case analysis, the themes of the rural effect on science education, the administrative effect, the effect of standards and assessments, and the effects of school improvement on science teachers were identified and explored. Findings of the research indicate that rural teachers will often remain in a position because of their family and community ties to a location regardless of their current working environment. Teacher satisfaction is determined by their ability to help students succeed in life, and not on standardized tests. Finally, the administration’s ability to mediate school reform and understand the school culture is imperative for school improvement to occur. The implementation of the Common Core State Standards and the Next Generation Science Standards has the potential to change the face of education in the United States, but the potential may be unfulfilled if teachers are not empowered to implement the standards with fidelity.
A Dissertation submitted to the Graduate School Valdosta State University in partial fulfillment of requirements for the degree of DOCTOR OF EDUCATION in Curriculum and Instruction in the Department of Curriculum, Leadership, and Technology of the Dewar College of Education and Human Services July 2013
Keywords: Curriculum and Instruction; Education -- teacher motivation; Common Core State Standards; Next Generation Science Standards; Education -- teacher satisfaction; Education -- reform